LEVERAGING INNOVATION TO ENHANCE SUPPLY CHAIN PERFORMANCE IN INDONESIAN MANUFACTURING: THE ROLES OF TECHNOLOGY, QUALITY MANAGEMENT, AND OPERATIONAL CAPABILITY - Jeff, Joanito Tony; Achmadi, Hendra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Indonesia's manufacturing sector faces significant challenges due to deficiencies in quality management and information technology (IT) innovation. The objectives of this research are to analyze the influence of Supply Chain Operational Abilities, Supply Chain Technology and Quality Management on Innovation Capability. Also investigate the mediation effect of Innovation Capability on the impact of Supply Chain Operational Abilities, Supply Chain Technology, and Quality Management on Supply Chain Performance. This study is quantitative research and, based on its objectives, it belongs to the type of explanatory research. The population of this research is the supply chain department employees in manufacturing companies in Indonesia with 330 respondents as the research sample. This research uses partial least squares-structural equation model (PLS-SEM) regression analysis to test the hypothesis. Research results demonstrated that Supply Chain Operational Abilities and Supply Chain Technology have a significant positive effect on Supply Chain Performance, but Quality Management does not significantly affect Supply Chain Performance directly. Innovation Capability serves as a significant mediator for the impact of Supply Chain Operational Abilities, Supply Chain Technology and quality management on Supply Chain Performance.